Observation of the B-s(0) -> X(3872)phi Decay - (:unkn) unknown (AMER PHYSICAL SOC, 2020)
Using a data sample of proton-proton collisions at root s = 13 TeV, corresponding to an integrated luminosity of 140 fb(-1) collected by the CMS experiment in 2016-2018, the B-s(0) -> X(3872)phi decay is observed. Decays into J/psi pi(+)pi(-) and K+K- are used to reconstruct, respectively, the X(3872) and phi. The ratio of the product of branching fractions B[B-s(0) -> X(3872)phi]B[X(3872) -> J/psi pi(+)pi(-)] to the product B[B-s(0) ->psi(2S)phi]B[psi(2S) -> J/psi pi(+)pi(-)] is measured to be [2.21 +/- 0.29(stat) +/- 0.17(syst)]%. The ratio B[B-s(0) -> X(3872)phi]/B[B-0 -> X(3872)K-0] is found to be consistent with one, while the ratio B[B-s(0) -> X(3872)phi]/B[B+-> X(3872)K+] is two times smaller. This suggests a difference in the production dynamics of the X(3872) in B-0 and B(0)s meson decays compared to B+. The reported observation may shed new light on the nature of the X(3872) particle.
Keywords: QED RADIATIVE-CORRECTIONS; UNIVERSAL MONTE-CARLO; PHOTOS